Status and factors influencing health-related quality of life in patients with non-alcoholic fatty liver disease in Hangzhou: a cross-sectional study - Junping Shi; Wei Zhang; Run Zhou; Tingting Kong; Kexin Lv; Yunpeng Gu; Yutong Chen; Yuna Shao (BMJ Open)
Objective Due to rapid economic development and the unique lifestyles, cultures and customs of Hangzhou, non-alcoholic fatty liver disease (NAFLD) has attracted widespread attention, with a prevalence rate of 35–45%. In this study, we used the Chinese version of the Chronic Liver Disease Questionnaire for NAFLD (CLDQ-NAFLD) to investigate the current health-related quality of life (HRQL) among patients with NAFLD and analyse the influencing factors, which provides a reference for improving the patients’ HRQL.Design A cross-sectional design.Setting This study was conducted from March 2022 to March 2023 at a tertiary hospital in Hangzhou.Participants All patients with NAFLD included in this study were diagnosed using FibroScan, with a controlled attenuation parameter ≥248 dB/m.Primary outcome measures The primary outcome of the study was the HRQL score, which was assessed using the Chinese version of the CLDQ-NAFLD.Results A total of 502 patients with NAFLD were enrolled in this study (mean age 1.79±13.49 years; 69.7% male). The overall HRQL score was 5.89 (5.33, 6.36), and the fatigue dimension score was the lowest at 5.17 (4.33, 6.00). Multiple linear regression analyses revealed that poor HRQL score was correlated with other marital status (β=−0.096, p=0.036), liver stiffness ≥10.3 (kPa) (β=−0.110, p=0.017), regular exercise (β=−0.121, p=0.006), sex (β=−0.114, p=0.012) and alanine transaminase (ALT) levels (β=−0.139, p=0.002). A monthly income >10 000 (renminbi) was associated with a significantly higher HRQL score.Conclusions This cross-sectional survey conducted in Hangzhou, China, revealed that HRQL is impaired among patients with NAFLD. This study revealed a significant association between HRQL and sociodemographic factors, including sex, monthly income and marital status, alongside clinical factors such as liver stiffness, regular exercise and ALT level. Emphasising optimal care management is essential to improve HRQL in patients with NAFLD.